Implementation and Evaluation of Resuscitation Training for Childcare Workers - Michel, Jörg; Ilg, Tim; Neunhoeffer, Felix; Hofbeck, Michael; Heimberg, Ellen (Frontiers in Pediatrics, 2022)
Background and Objective Children spend a large amount of time in daycare centers or schools. Therefore, it makes sense to train caregivers well in first-aid measures in children. The aim of this study is to evaluate whether a multimodal resuscitation training for childcare workers can teach adherence to resuscitation guidelines in a sustainable way. Materials and Methods Caregivers at a daycare center who had previously completed a first-aid course received a newly developed multimodal resuscitation training in small groups of 7–8 participants by 3 AHA certified PALS instructors and providers. The 4-h focused retraining consisted of a theoretical component, expert modeling, resuscitation exercises on pediatric manikins (Laerdal Resusci Baby QCPR), and simulated emergency scenarios. Adherence to resuscitation guidelines was compared before retraining, immediately after training, and after 6 months. This included evaluation of chest compressions per round, chest compression rate, compression depth, full chest recoil, no-flow time, and success of rescue breaths. For better comparability and interpretation of the results, the parameters were evaluated both separately and summarized in a resuscitation score reflecting the overall adherence to the guidelines. Results A total of 101 simulated cardiopulmonary resuscitations were evaluated in 39 participants. In comparison to pre-retraining, chest compressions per round (15.0 [10.0–29.0] vs. 30.0 [30.0–30.0], p < 0.001), chest compression rate (100.0 [75.0–120.0] vs. 112.5 [105–120.0], p < 0.001), correct compression depth (6.7% [0.0–100.0] vs. 100.0% [100.0–100.0], p < 0.001), no-flow time (7.0 s. [5.0–9.0] vs. 4.0 s. [3.0–5.0], p < 0.001), success of rescue breaths (0.0% [0.0–0.0] vs. 100.0% [100.0–100.0], p < 0.001), and resuscitation score were significantly improved immediately after training (3.9 [3.2–4.9] vs. 6.3 [5.6–6.7], p < 0.001). At follow-up, there was no significant change in chest compression rate and success of rescue breaths. Chest compressions per round (30.0 [15.0–30.0], p < 0.001), no-flow time (5.0 s. [4.0–8.0], p < 0.001), compression depths (100.0% [96.7–100.0], p < 0.001), and resuscitation score worsened again after 6 months (5.7 [4.7–6.4], p = 0.03). However, the results were still significantly better compared to pre-retraining. Conclusion Our multimodal cardiopulmonary resuscitation training program for caregivers is effective to increase the resuscitation performance immediately after training. Although the effect diminishes after 6 months, adherence to resuscitation guidelines was significantly better than before retraining.